The impact of changing accounting policies on profitability determination in Algerian Enterprises: A field study - Khemgani, Abdelhadi; Bellaouar, Slimane (The International tax journal, 2025)
This study aimed to analyze the impact of accounting policies on determining profitability in Algerian institutions. To achieve this goal, we adopted a descriptive approach, conducting a field study on a sample of accountants using a questionnaire. The questionnaire was distributed to a sample of 141 respondents from the targeted job categories in Algerian institutions. Data were analyzed using Pearson's correlation coefficient to test internal consistency, as well as Kruskal-Wallis and Mann-Whitney tests to measure differences between groups based on experience. The results showed that Algerian institutions are changing their accounting policies, such as inventory valuation methods, depreciation methods, and recognition practices. Accounting flexibility is sometimes used as a strategic tool for managing profitability in institutions, but to varying degrees among institutions, with little flexibility regarding depreciation practices for profit purposes. The study recommended enhancing accounting flexibility by developing policies that allow for adaptation to economic and legislative changes without compromising the reliability of accounting information.